New TRUS Techniques and Imaging Features of PI-RADS 4 or 5: Influence on Tumor Targeting - Chang, Amy Inji; Park, Byung Kwan (Frontiers in Oncology, 2021)
Purpose: To determine if the new transrectal ultrasound (TRUS) techniques and imaging features improve contribute to targeting Prostate Imaging and Reporting and Data System (PI-RADS) 4 or 5. Materials and Methods: Between December 2018 and February 2020, 115 men underwent cognitive biopsy by radiologist A, who was familiar with the new TRUS findings and biopsy techniques. During the same period, 179 men underwent magnetic resonance imaging–TRUS image fusion or cognitive biopsy by radiologist B, who was unfamiliar with the new biopsy techniques. Prior to biopsy, both radiologists knew MRI findings such as the location, size, and shape of PI-RADS 4 or 5. We recorded how many target biopsies were performed without systematic biopsy and how many of these detected higher Gleason score (GS) than those detected by systematic biopsy. The numbers of biopsy cores were also obtained. Fisher Exact or Mann-Whitney test was used for statistical analysis. Results: For PI-RADS 4, target biopsy alone was performed in 0% (0/84) by radiologist A and 0.8% (1/127) by radiologist B (p>0.9999). Target biopsy yielded higher GSs in 57.7% (30/52) by radiologist A and 29.5% (23/78) by radiologist B (p=0.0019). For PI-RADS 5, target biopsy alone was performed in 29.0% (9/31) by radiologist A and 1.9% (1/52) by radiologist B (p=0.0004). Target biopsy yielded higher GSs in 50.0% (14/28) by radiologist A and 18.2% (8/44) by radiologist B (p=0.0079). Radiologist A sampled fewer biopsy cores than radiologist B (p=0.0008 and 0.0023 for PI-RADS 4 and 5, respectively. Conclusions: PI-RADS 4 or 5 can be more precisely targeted if the new TRUS biopsy techniques are applied.